Parameters lnfluencing Planning of District Level Towns in Bangladesh : A Case Study of Jhenaidah Town (Bangladesh Journal of Public Administration, 2021)
Town planning is a comprehensive task involving several stages that takes the city from actual state it is in to a desired state in the future through various measures taken by the concerned planning authorities. A city may be viewed as a system or a complex whole consisting of different component parts related or interacting with one another so as to form a unity. The component parts of the systenl consists of persistent human activities that have a tendency to occur or recur at specific locations that is, the activities occur within adopted spaces which include buildings, parks, water, bodies etc. The co~l~leclionasm ong these parts are communications which enable various activities to inter;ict so that necessary patterns of huinan behaviour can occur. These communications are recurrent and spatially clustered such as roads, railn~aysp, ipelines, cables etc. Implemelltation of the plan involves control of the various components of thissystenl so that the intended state as set out by the goals of the plan would depend on the existing state of the city. Therefore a thorough knowledge of the present state of the city is the first and an ilnportant step in any planning process.